Coping with negative mental images in social anxiety disorder: Investigating the potential benefits of image morphing. Issue 1 (17th January 2019) - Vidovic, Vanja; Romano, Mia; Moscovitch, David A.
Negative mental imagery contributes to symptom maintenance in social anxiety disorder (SAD). Here, we investigated the effects of image morphing, a brief mental strategy designed to facilitate access to positive images. Participants with SAD and healthy control (HC) participants were randomly assigned to receive either image morphing or supportive counseling. Although initial training and 1-week daily practice were successful in equipping morphing participants across groups with the required skill, those assigned to morphing failed to demonstrate differential improvements in positive affect, negative affect, or self-perception relative to control participants during a subsequent social stress task. Ancillary analyses revealed that the number of positive details contained in retrieved or morphed images prior to the task significantly predicted the level of positive affect reported after the task, but this effect was observed only for HC participants. We discuss the need for future research to refine innovative imagery-based psychotherapeutic strategies for social anxiety.